IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU DALAM MENGELOLA PEMBELAJARAN PADA MATA PELAJARAN PAI DI SMP AL-AZHAR MANDIRI PALU - Sakinah, Nur; Gusnarib; M. Arif, Arifuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of teachers' pedagogical competence in managing learning in the Islamic Religious Education subject at Al-Azhar Mandiri Junior High School Palu, and the impact of teachers' pedagogical competence in managing learning in the Islamic Religious Education subject at Al-Azhar Mandiri Junior High School, Palu. This study uses a qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of pedagogical competence includes: Understanding student characteristics through diagnostic assessments and direct observation during the learning process. Learning planning and curriculum development through MGMP (Subject Teacher Consultation Forum) to design and prepare teaching modules in determining TP (learning objectives) and ATP (learning objective flow) by adjusting the elements in CP (learning outcomes). The implementation of innovative learning by applying the PJBL method, group discussions, and the use of technology in learning such as Canva and audio-visual media, although it has not yet been fully maximized in the learning process. The implementation of comprehensive evaluations includes diagnostic, formative, and summative assessments. The impact of implementing teachers' pedagogical competence in learning management contributes to the achievement of learning objectives because the learning practices applied are adjusted to the characteristics and needs of students. In addition, there is an improvement in students' character and achievement. These findings indicate that teachers' pedagogical competence has an impact on achieving learning objectives and shaping students' character in accordance with Islamic teachings through continuous training and school support.